2018
DOI: 10.1002/ab.21757
|View full text |Cite
|
Sign up to set email alerts
|

Reactive aggression tracks within‐participant changes in women's salivary testosterone

Abstract: The relation between testosterone and aggression has been relatively well documented in men, but it is less well understood in women. Here we assessed the relationship between salivary testosterone and reactive aggression (i.e., rejection rate for unfair offers) in the Ultimatum Game. Forty naturally cycling women were tested twice, once in the late follicular phase (around ovulation) and once during the luteal phase. Ovulation was determined using urine test strips measuring luteinizing hormone levels. Saliva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 71 publications
0
9
0
Order By: Relevance
“…Despite these mean differences, the authors found positive correlations between testosterone and self-reported aggression in both women and men. Thus, although aggression and testosterone may be lower in women than men, many studies observed the same positive relationships between testosterone and aggression in women as they do in men (e.g., Prasad et al, 2017 ; Probst et al, 2018 ). A study of 12 women in a double-blind placebo-controlled testosterone administration study suggests that testosterone may increase aggression because it reduces sensitivity to punishment and increases reward sensitivity (van Honk et al, 2004 ).…”
Section: Part 2: Neurobiological Pathways To Women’s Aggressionmentioning
confidence: 93%
“…Despite these mean differences, the authors found positive correlations between testosterone and self-reported aggression in both women and men. Thus, although aggression and testosterone may be lower in women than men, many studies observed the same positive relationships between testosterone and aggression in women as they do in men (e.g., Prasad et al, 2017 ; Probst et al, 2018 ). A study of 12 women in a double-blind placebo-controlled testosterone administration study suggests that testosterone may increase aggression because it reduces sensitivity to punishment and increases reward sensitivity (van Honk et al, 2004 ).…”
Section: Part 2: Neurobiological Pathways To Women’s Aggressionmentioning
confidence: 93%
“…It is known that in bitches, the ovaries are sites of testosterone production [ 14 , 21 ]. Recently, in a study on women, the authors suggested that an aggressive response to provocation was related to high levels of testosterone in saliva [ 22 ]. Plasma progesterone levels have been reported to be lower in neutered than intact dogs of both genders [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…Studies about these relationships are scarce in the field. However, there is evidence about the effect of testosterone on aggressive behavior in women [ 27 , 28 ] (for a negative effect, see [ 58 ]) and about the use of indirect forms of aggression to compete for status [ 18 ], justifying our expectations. This lack of relationships could arise for the same reasons in women as for men, evidencing the need to apply a more complex design including personality traits as mediators and experimental manipulations to investigate causal relationships between the use of aggression and changes in social status.…”
Section: Discussionmentioning
confidence: 92%
“…For example, testosterone facilitates aggression in animals [ 23 , 24 , 25 ], and, since the 1980s, it has been considered a social hormone that influences behavior in situations linked to the maintenance or enhancement of social status [ 26 ]. However, the principal evidence of a direct relationship between aggression and testosterone came from studies in men [ 27 ], being less investigated in women (see [ 27 , 28 ]). The studies about genetic sensitivity to testosterone have opened a new research avenue.…”
Section: Introductionmentioning
confidence: 99%